Back To The Future: Hinton v Donaldson, Wood and Meurose (Court of Session, Scotland, 28th July, 1773) (Journal of Open Law, Technology & Society, 2010)
History moves in cycles, and recent debate around the extent and term of copyright is no exception to this rule. There are two forces at play, one being the view that knowledge is of value and indeed belongs to all mankind, and the other being that knowledge, as a creation of individuals, is property to be regulated and shared according to the wishes of its owner. This case law report examines the debate through a different lens, moving back from software and the Internet in favour of Stackhouse's History of the Holy Bible, Scottish printers and the year 1773.